Mammalian genomics [ - Graves, J. A. Marshall [ (Jennifer A. Marshall)]; Ruvinsky, Anatoly (CABI, 2004)
Genomics has experienced a dramatic development during the last 15-20 years. Data from mammalian genomes such as the human, mouse and rat have already been published, while others such as the dog, cattle and chimpanzee will soon follow. This book summarizes the current knowledge of mammalian genomics and offers a comparative analysis of genomes known today. This analysis includes farm, companion and lab animals. Topics covered include structural and functional aspects of the mammalian genome, mechanisms of genomic changes at the molecular level, evolution of DNA sequences, comparative chromosome mapping and painting, genome databases, gene prediction and the use of genomic information to understand inherited diseases. Contributors include leading researchers from Europe, USA, Australia and Japan.